Dramatising History in Schoepper's Ioannes Decollatus and Grimald's Archipropheta - Pincombe, Michael (Staging History, 2021)
The two neo-Latin versions of the martyrdom of John the Baptist, Jacob Schoepper's loannes decollatus and Nicholas Grimald's Archipmpheta, show adaptations of a biblical 'history' to tragic modes. Operating a distinction between veracity and verisimilitude, the plays follow classical practice, yet at the same time they also aim to offer a response to ordinary circumstances, such as a classroom environment. This exemplarity is a feature centred upon the presentation of Herod and Herodias as monsters with didactic value.
CRIS-Team WoS Importer:2022-09-30

The clerical career of the poet and translator John Studley - Pincombe, Michael (Notes and queries, 2020)
CRIS-Team Scopus Importer:2020-12-11